2012
DOI: 10.1120/jacmp.v13i5.3837
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficiency and effectiveness of independent dose calculation followed by machine log file analysis against conventional measurement based IMRT QA

Abstract: Experimental methods are commonly used for patient‐specific IMRT delivery verification. There are a variety of IMRT QA techniques which have been proposed and clinically used with a common understanding that not one single method can detect all possible errors. The aim of this work was to compare the efficiency and effectiveness of independent dose calculation followed by machine log file analysis to conventional measurement‐based methods in detecting errors in IMRT delivery. Sixteen IMRT treatment plans (5 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 30 publications
0
53
0
2
Order By: Relevance
“…Although not based on direct dosimetric measurements, post-treatment or real-time monitoring of MLC log files is a simpler solution. This approach has been demonstrated by several groups 16,22 and log-file QA software is now commercially available for use in the clinic (Modus Medical Devices, Inc.). It has been suggested that supplementing MLC log file analysis with independent dose calculations may be a better QA method than traditional measurement-based approaches due to increased sensitivity to dose calculation errors, heterogeneity errors, and beam modeling errors.…”
Section: D Quality Control Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not based on direct dosimetric measurements, post-treatment or real-time monitoring of MLC log files is a simpler solution. This approach has been demonstrated by several groups 16,22 and log-file QA software is now commercially available for use in the clinic (Modus Medical Devices, Inc.). It has been suggested that supplementing MLC log file analysis with independent dose calculations may be a better QA method than traditional measurement-based approaches due to increased sensitivity to dose calculation errors, heterogeneity errors, and beam modeling errors.…”
Section: D Quality Control Strategiesmentioning
confidence: 99%
“…Comparison of machine delivery log files to planned patterns could reveal failures-a practice that has been shown to be both feasible and effective for postdelivery verification. 16 This approach is also much less resource intensive than physical measurement-based QA. Retrospective post-treatment QA (simulated or physical phantom-based) could be adequate for delivery systems that demonstrate time-tested stability.…”
Section: D Quality Control Strategiesmentioning
confidence: 99%
“…Several groups have proposed the use of machine log file analysis as an alternative for IMRT and VMAT QA [8]- [10]. However, log file evaluation must be performed after VMAT delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Nosúltimos anos, o cálculo de dose independente do SPT vem sendo apresentado como uma forma de realizar o CQ de IMRT com uma redução da carga de trabalho [38,39,32,40,41]. A propostaé substituir a dosimetria por esse cálculo, como forma de verificar as previsões dosimétricas do SPT.…”
Section: Controle De Qualidade De Imrtunclassified
“…O cálculo independente não verifica a entrega da dose, portanto, esse método deve ser acompanhado de uma outra forma de verificar o funcionamento da máquina de tratamento. Essa verificação pode ser realizada por meio de um arquivo (log file) que possui informações, adquiridas pelos sistemas de detecção do acelerador linear, de parâmetros usados na irradiação, como o posicionamento do MLC [39]. Diferentes algoritmos de cálculo são usados na implementação dos sistemas de cálculo independente, sendo os métodos baseados em simulações de Monte Carlo os que proporcionam maior exatidão.…”
Section: Controle De Qualidade De Imrtunclassified